Clinical manifestations of bed bug bites: A systematic review of case reports - Julian Felipe Porras-Villamil; Zachary C. DeVries (PLoS ONE, 2026)
Importance Clinical characterization of bed bug ( Cimex spp.) bite manifestations remains limited. Objective This systematic review synthesizes case reports to describe dermatological, systemic, and psychological outcomes of bed bug bites. Evidence review Following PRISMA guidelines, multiple databases, including Pubmed and Scopus, were searched using terms such as “bed bug,” “ Cimex lectularius ,” “ Cimex hemipterus ,” “case report,” and “case series.” Extracted data included demographics, species, lesion type, anatomical distribution, and clinical manifestations. Quantitative and qualitative analyses were conducted. Results Eighty-four patients were included: 76 with C. lectularius (90.5%) and, 8 with C. hemipterus (9.5%). Sex distribution was balanced (47.6% females, 52.4% males), and mean ages were similar (females 37.5 ± 22.1, males 42.3 ± 21.27 years; p = 0.332). Extremities were commonly affected, arms were reported in 71.4% of cases, legs in 59.5% and trunk in 34.5%. Psychological symptoms were registered in a handful of case reports (Anxiety 9.5%, Stress 9.5%, Hopelessness 9.5%). Systemic symptoms, generally associated with anemia, were reported in cases related to severe infestations in neglected patients. Some differences in systemic and local signs and symptoms were detected depending on age group. Conclusions Bed bug bites predominantly affect exposed extremities, although with variable dermatologic patterns that can be confused with other arthropod bites. Psychological manifestations were reported in a small subset of cases, while systemic complications were rare.